2022
DOI: 10.3390/cancers14092081
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Systemic Inflammation Markers in Intrahepatic Recurrence of Early-Stage Hepatocellular Carcinoma after Curative Treatment

Abstract: Systemic inflammatory markers (SIMs) are known to be associated with carcinogenesis and prognosis of hepatocellular carcinoma (HCC). We evaluated the significance of SIMs in intrahepatic recurrence (IHR) of early-stage HCC after curative treatment. This study was performed using prospectively collected registry data of newly diagnosed, previously untreated HCC between 2005 and 2017 at a single institution. Inclusion criteria were patients with Barcelona Clinic Liver Cancer stage 0 or A, who underwent curative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…of 2.46 (95% C.I. 1.60–3.79) for early recurrence after ablation treatment [ 48 ], while Bae et al [ 49 ] found that male gender has an H.R. of 1.35 (95% C.I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…of 2.46 (95% C.I. 1.60–3.79) for early recurrence after ablation treatment [ 48 ], while Bae et al [ 49 ] found that male gender has an H.R. of 1.35 (95% C.I.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with HCC, a low LMR is associated with worse outcomes and an increased risk of recurrence [ 73 ]. However, studied LMR cut-offs are highly variable in each study, thus determining a low reproducibility [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that a high PLR may be related to early distant recurrence, poor overall survival, and tumor aggressiveness [ 20 , 25 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Here, we investigated whether serum markers are useful for the prediction of clinical outcomes (especially for DM) in patients with unresectable HCC receiving curative RT in the contemporary era.…”
Section: Introductionmentioning
confidence: 99%
“…Platelet to lymphocyte count ratio (PLR) is a novel biomarker that has been initially proposed as an ideal indicator of systemic inflammation [11][12][13]. Recently, emerging evidence indicated strong link in between OSAHS, liver diseases (including HBV/HCV and HCC), and PLR [14][15][16][17]. However, there was a lack of data regarding the association between PLR and NAFLD.…”
Section: Introductionmentioning
confidence: 99%